Effects of volume fraction on water-based carbon nanotubes flow in a right-angle trapezoidal cavity: FEM based analysis. (July 2020) - Khan, Zafar H.; Khan, Waqar A.; Haq, R.U.; Usman, M.; Hamid, M.
Abstract: The purpose of the current study is to investigate the effects of water-based single-walled carbon nanotubes on free convection in a partially heated right trapezoidal cavity. The bottom wall of the cavity is heated while the side walls are kept cold, and the top wall is adiabatic. The governing dimensionless partial differential equations are solved with selected dimensionless boundary conditions via finite element scheme. The effects of the heating domain, the volume fraction of carbon nanotubes, Rayleigh and Hartmann numbers on the streamlines, isotherms, dimensionless horizontal and vertical velocities, dimensionless temperature and the local Nusselt number along the heating element are investigated numerically. The strength of streamlines decreases with increasing values of volume fraction of CNTs and Hartmann number while an enhanced behavior is noted for higher values of Rayleigh number and increasing the length of the heating element. The isotherms confirm the transfer of heat from bottom to side cold walls. It is demonstrated that the local Nusselt number attains the maximum values around the edges of the heating element and then decreases. Furthermore, the heating domain and the carbon nanotubes enhance the local Nusselt number along the heated surface.